Collaborative Learning and Communication Among Muslim Students at an Islamic University: A Gender Perspective - Kurnia Santi; Irwandani; Nur Habib Muhammad Iqbal (WISE Pendidikan Indonesia, 2024)
This research aims to assess the communication and collaboration skills of Muslim students, with a specific focus on gender-related, especially, women’s perspectives. A mixed-methods approach was employed, combining quantitative measurements for analyzing students' communication and collaboration skills with qualitative methods, including observations and in-depth interviews, to gain insights into the influence of gender and Islamic understanding on these skills. The study findings revealed that, within the context of Islamic education, women tend to demonstrate stronger verbal communication skills, while men excel in nonverbal communication and collaboration. Essential factors contributing to effective communication and collaboration skills include adherence to communication norms, the use of polite language, and a keen awareness of Islamic social conventions. Additionally, differences in gender roles within Muslim societies were identified as influential in shaping communication patterns and collaboration dynamics. To promote inclusivity and respect for diversity, Islamic higher education institutions should strive to create an environment where both men and women can freely exchange ideas, thoughts, and knowledge without constraints. By advancing gender equality, Islamic higher education can contribute to the development of capable future leaders, uphold Islamic values, and contribute to the establishment of a just and sustainable society.